OCA Java SE 8 programmer I exam guide (exam 1Z0-808) - Sierra, Kathy; Bates, Bert (New York McGraw-Hill Education, 2017)
Up-to-date coverage of every topic on the Java 8 SE Programmer I exam Prepare for the OCA Java SE 8 Programmer I exam using this effective self-study system from Oracle Press. Written by developers of the original Sun Certified Java Programmer exam, OCA Java SE 8 Programmer I Exam Guide (Exam 1Z0-808) includes two complete, accurate practice exams. In all, you will get more than 200 practice questions that mirror those on the actual test in content, tone, and format. Beyond fully preparing you for the challenging exam, the book also serves as an ideal on-the-job reference. Clearly explains every topic on Exam IZ0-808, including: Declarations Access control Object orientation Assignments Operators Flow control Exceptions Strings Arrays ArrayLists CD ICON Electronic content includes: 200+ practice exam questions Fully customizable test engine Secured book PDF.
Includes index.
At head of title: Oracle, Oracle Press.
Keywords: Java (Computer program language) -- Examinations -- Study guides